Determining Book Distribution Routes by Implementing Vehicle Routing Problems Using Excel Solver at Gunadarma University - Boru Butar Butar, Maulida; Medikano, Alsen; Zulkarnain, Yahya (Pt. Anagata Sembagi Education, 2024)
Gunadarma University operates multiple campuses, each equipped with its own library. To ensure equitable access to newly acquired titles, it is imperative that these materials are disseminated across all campus libraries. So, when a new book title is added, this book must also be owned by the library at each campus location. In this research, book distribution routes with the shortest distance and time will be determined using the Vehicle Routing Problem (VRP) method with Excel Solver. Gunadarma University has a central library which is the starting point for distributing books to other campuses. The central university library serves as the distribution hub, from which books are dispatched to seven additional campus locations. Simulation results using Excel Solver showed that the shortest route for sending books to seven library locations on the Gunadarma University campus using one vehicle was a distance of 137.14 km in 3 hours 12 minutes. This optimized route yielded substantial cost savings, amounting to a 12.5% reduction compared to previous distribution practices.